Implementation of Multimedia-Based Two Stay Two Stray Type Cooperative Learning Method in Improving Student Learning Outcomes in the PAI Subject of Class X SMKN 2 Bengkulu City - Agus pahernita (Journal of Islamic Pedagogy and Educational Development, 2025)
Background: This study aims to determine whether the application of the cooperative learning method type two stay two stray based on multimedia can improve student learning outcomes in the subject of Islamic Religious Education class X SMKN 2 Bengkulu City, to find out how the learning outcomes of class X students of SMKN 2 Bengkulu City who use the cooperative learning method type two stay two stray based on multimedia. Method: This type of research is classroom action research. data collection methods are observation, documentation and tests, from the results of the study it was concluded that the application of the cooperative method type two stay two stray based on multimedia can improve student learning outcomes in Islamic Religious Education subjects. Results: This is proven by the results of the pre-cycle test, the average value achieved by students was 66.92 with a percentage of 28%, then in cycle 1 it increased to an average value of 69.88 and a percentage of 40% but was still below standard and increased in cycle 11 with an average value of 75.6 and a percentage of 76%. Conclusion: With the increase in student learning outcomes, the use of the multimedia-based two stay two stray cooperative method can improve student learning outcomes in Islamic Religious Education subjects at Smkn 2 Bengkulu City.